Two women and one destiny: Mexico - Fernández Poncela, Ana María (2025)
The objective of this text is to provide a general account of figures and information about women presidents in the world and Latin America. It focuses on the candidates in the history of Mexico and the 2024 elections. To achieve this, a bibliographic and documentary review is conducted. The findings indicate that there are few women presidents in general and that the candidacies in Mexico have been reduced, also presented by political forces with little chance of victory. For the year 2024, two women have emerged with a real chance of triumph, so the destiny of one will be to preside over the country, and the destiny of Mexico to be governed by a woman.